ANALISIS PESAN KOMUNIKASI DALAM SURAT LUQMAN AYAT 12-19 - Jasyadi, ahmad (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2018)
This paper analyzes Luqmanul Hakim’s communication message against his son in the Qur’an of Luqman’s letter verses 12-19 based on Tafsir Jalalain. In addition, this paper also aims to fnd out how the opinion of the scholars of the Tafsir (Jalaluddin al-Mahalli and Jalaluddin as-Suyuthi) about Luqman’s message, especially in the context of the verse in Luqman’s letter, to broaden the knowledge of the meaning of Luqmanul Hakim’s communications message. This paper is, a research that has been done in literature research. Message analysis procedures using Qualitative Content. Methods in religious studies or Islamic history contained in the Qur’an that use ma’tsur and ra’y. This study uses a qualitative type because it deepens deeper into the message of a Luqmanul Hakim, especially in the context of verses 12-19 of Luqman’s letter with content analysis